2017
DOI: 10.1007/s10961-017-9617-5
|View full text |Cite
|
Sign up to set email alerts
|

Cluster ambidexterity towards exploration and exploitation: strategies and cluster management

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 37 publications
2
49
0
1
Order By: Relevance
“…I4.0 as specific disruptive innovation builds among others on the firm's ambidexterity, i. e. the skills to balance the knowledge exploitation and exploration. As the study by Wolf et al (2019) revealed that cluster management could help cluster companies to become more ambidextrous. Hence, it might be expected, that this assistance translates into improved conditions for digital transformation.…”
Section: Institut Für Kunststoffverarbeitung (Ikv) Aachenmentioning
confidence: 99%
See 1 more Smart Citation
“…I4.0 as specific disruptive innovation builds among others on the firm's ambidexterity, i. e. the skills to balance the knowledge exploitation and exploration. As the study by Wolf et al (2019) revealed that cluster management could help cluster companies to become more ambidextrous. Hence, it might be expected, that this assistance translates into improved conditions for digital transformation.…”
Section: Institut Für Kunststoffverarbeitung (Ikv) Aachenmentioning
confidence: 99%
“…The literature on geographical aspects of digital transformation seems to be still in its infancy (Alcácer et al, 2016;Montresor and Antonietti, 2019). While recent research on clusters seeking to map the future trajectories takes into account new aspects of related problems of innovativeness or knowledge networks (Lazzeretti et al, 2019;Wolf et al, 2019).…”
Section: Institut Für Kunststoffverarbeitung (Ikv) Aachenmentioning
confidence: 99%
“…While minor incremental improvements of an existing technological solution are calculable and can be integrated in the planning processes of firms, abrupt changes of technology present them with major challenges that are beyond the predictability of any established planning framework. The research literature has coined the term "ambidexterity" to describe the capability to meet these challenges without disrupting routine activities (see, for instance, Wolf et al, 2019). This concept originally addressed the behavioural patterns of firms, but it is obvious that it also applies to Triple Helices and the research organisations and government authorities involved.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…"Clustering" of the Economy vs. kairos Clusters in German Cluster Policies In this section, we look at the role of kairos constellations in the practical application of cluster policy in Germany. The discussion is based on three types of sources: interviews conducted by the authors as a part of various research projects with government officials responsible for cluster promotion programmes and stakeholder of these programmes, an analysis of government publications on cluster policy, and several academic studies (Beck 2014;Dohse 2000Dohse , 2007Dohse and Staehler 2008;Fornahl et al 2010;Fornahl et al 2012, Fornahl et al 2015Frommhold-Eisebith 2014;Kiese 2012Kiese , 2014Kiese , 2017Uyarra and Ramlogan 2016;Wolf et al 2019).…”
Section: 3mentioning
confidence: 99%
“…(3) Studies dealing with selected aspects of cluster policy impact using methods of econometric causal analysis (e.g., Engel et al 2017;Nestle 2011). (4) Econometric analyses of specific aspects of the impacts of promoted clusters, such as the development of ensuing innovation networks (e.g., Graf and Broekel 2020;Cantner et al 2013;Wolf et al 2017), or studies that use qualitative methods to analyse special dimensions of cluster development, for instance, the importance of cluster initiatives for regional economic development (Kiese and Hundt 2014).…”
Section: Cluster Policy Evaluationsmentioning
confidence: 99%